Numerical analysis of non-Fourier thermal response of lung tissue based on experimental data with application in laser therapy. (February 2021) - Eltejaei, Iman; Balavand, Mohsen; Mojra, Afsaneh
Highlights: Non-Fourier thermal response of lung specimens is noticed through experiments. A numerical code is developed to simulate Fourier and non-Fourier heat transfer. Experimental results indicate an average value of 1.17 ± 0.05 s for the phase lag of heat flux. The optimum value for the phase lag of temperature gradient is obtained to be 20.53 ± 2.19 s . Necrotized area during laser therapy is reduced by 21% considering the phase lags. Abstract: Background and objective: The thermal therapy is a minimally invasive technique used as an alternative approach to conventional cancer treatments. There is an increasing concern about the accuracy of the thermal simulation during the process of tumor ablation. This study is aimed at investigating the effect of finite speed of heat propagation in the biological lung tissue, experimentally and numerically. Methods: In the experimental study, a boundary heat flux is applied to the lung tissue specimens and the temperature variation is measured during a transient heat transfer procedure. In the numerical study, a code is developed based on the finite volume method to solve the classical bio-heat transfer, the Cattaneo and Vernotte, and the Dual-phase-lag (DPL) equations. The thermal response of tissue during the experiments is compared with the predictions of the three heat transfer models. Results: It is found that the trend of temperature variation by the DPL model resembles the experimental results. The experimental observation in parallel with the numerical results reveals that the accumulated thermal energy diffuses to the surrounding tissue with a slower rate in comparison with the conventional bio-heat transfer model. The DPL model is implemented to study the temperature elevation in the laser irradiation to lung tissue in the presence of gold nanoparticles (GNPs). It is concluded that the extent of the necrotic tumoral region and the area of the damaged healthy tissue are reduced, when the non-Fourier heat transfer is taken into account. Conclusions: Results show that considering the phase lags is crucial in planning for an effective thermal treatment, in which the cancerous tissue is ablated and the surrounding tissues are preserved from irreversible thermal damage.